Effects of the disappearance of Conasupo on trade and prices of staple crops - Yúñez Naude, Antonio; Barceinas, Fernando (Estudios Económicos de El Colegio de México, 2000)
This article examines one of many reforms undertaken by the Mexican government in order to liberalize the economy: the dismantling of Conasupo, which was probably the most important state trading enterprise of Mexico. In this article we document the steps followed to eliminate this company, with special emphasis on its effect on trade. We also present the results of an empirical investigation that indicated that as a consequence of the liberalization of Mexico’s agricultural sector, its food staple producers are now subject to international competition.